Penanganan Keluhan Tamu Oleh Room Attendant Dalam Menjaga Citra Hotel Di Jivana Resort Lombok - Sugiman Sugiman; Puspa Khaerani (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
This study aims to: to find out how to handle guest complaints, how to maintain the hotels citra and affect of handling guest complaints by the room attendant on the hotels citra at Jivana Resort Lombok. This research uses a qualitative descriptive method that uses survey and interview methods. The results of this study show in away Listen carefully to guests' complaints, do not interrupt ,Stay polite and say thank you because the guest has brought the problem to you, If necessary apologize for the incident that happened to him, Mention the guest's name so that they feel cared for, Focus your attention on the guest's problem, Immediately follow up the guest's complaint to the relevant section, Make sure the guest's complaint is followed up, check if it is in accordance with the wishes of the guest, Make clear policies, Address minor issues quickly to the relevant sections, Improve online reputation, Ensure that guest complaints are followed up, check whether they are in accordance with guests' wishes, while Jivana Resort Lombok's Citra is very good because the existing SOPs have been implemented in accordance with established standards, Handling every complaint that occurs is very influential on the citra of the hotel.